Environmental pollutants and the gut microbiota: mechanistic links from exposure to systemic disease - Ma, Wenjing; Xiong, Xiu; Tian, Zikun; Li, Lan; Huang, Yi (Frontiers in Microbiology, 2026)
Environmental pollution has emerged as a pervasive global health threat, yet its effects extend far beyond direct organ toxicity. Increasing evidence reveals that the gut microbiota serves as a central mediator of pollutant-induced physiological dysfunctions. This review integrates recent advances on how air pollutants, heavy metals, persistent organic pollutants, and emerging contaminants perturb microbial composition, metabolic activity, and host-microbe signaling. Pollutant exposure alters microbial-derived metabolites such as short-chain fatty acids, bile acids, and tryptophan derivatives, thereby impairing intestinal barrier integrity and immune homeostasis. These microbiota-driven disturbances trigger oxidative stress, chronic inflammation, and neuroendocrine dysregulation, contributing to metabolic disorders, immune imbalance, neurotoxicity, and carcinogenesis. Mechanistically, redox imbalance, activation of TLR4/NF-κB and NLRP3 pathways, and dysregulation of AhR signaling represent critical intersections linking environmental exposure to disease. By elucidating these molecular and ecological connections, this review underscores the gut microbiotaas a key target and therapeutic entry point for mitigating the health impacts of environmental pollution and guiding microbiota-based interventions for disease prevention.